2020
DOI: 10.1088/2043-6254/ab8b58
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of silver nanoparticles using Tualang honey and evaluation of their antioxidant activities

Abstract: Natural products are widely used in the synthesis of various types of metallic nanoparticles including silver nanoparticles. Tualang honey is one of the potential natural products which is rich in polyphenols and antioxidant capacity. This study aims to synthesise and characterise the silver nanoparticles by using Tualang honey through green method and evaluate their antioxidant activities. The formation of silver nanoparticles was examined by visual observation and further confirmed by UV-Visible spectrophoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…THSN was prepared via the green synthesis method. The synthesis and characterization of THSN are reported in our previous preliminary study 21 . The THSN was formulated in powder form and dissolved in 0.5 mL of distilled water before each use.…”
Section: Preparation Of Thsnmentioning
confidence: 99%
See 3 more Smart Citations
“…THSN was prepared via the green synthesis method. The synthesis and characterization of THSN are reported in our previous preliminary study 21 . The THSN was formulated in powder form and dissolved in 0.5 mL of distilled water before each use.…”
Section: Preparation Of Thsnmentioning
confidence: 99%
“…Recently, there has been emerging research interest in the plant-mediated green synthesis of silver nanoparticles due to their cost-effectiveness, environment-friendliness, and low toxicity profile compared to their hazardous chemicalmediated counterparts 19 . Few strategies have been explored to enhance honey's absorption and bioavailability, including the development of silver nanoparticles synthesized using Tualang honey (TH) formulations 20, 21 . In this study, we used Tualang honeymediated silver nanoparticles (THSN) to increase the bioactivity of the substance in the rat's brain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, it has been shown that metal nanoparticles (iron oxide) produced using the green synthesis routes have a much smaller average size (2 -80 nm) compared to that of particles produced using the synthetic chemical methods (87 -400 nm) Gokila et al (2021) 16 . We have previously synthesized silver nanoparticles using a green synthesis method, in which Tualang honey (TH) was used as the natural raw material 17 . TH is a well-known local honey that contains the highest level of antioxidant content compared to other local Malaysian honey 18 .…”
Section: Introductionmentioning
confidence: 99%